Teoría y práctica: una distinción inquietante - García Jiménez, Modesto (Nómadas. Critical Journal of Social and Juridical Sciences, 2006)
The Cartesian duality has historically shown a series of other dualities that supposedly should help us to “know” the reality. In the scientific knowledge a great number of opinions have arisen around the duality theory/praxis, to the point of exhausting a holistic idea about the manners in which the knowledge has been obtained, reconciling the theoretical and practical dimension as one. This article suggests, using one specific example, the risk of taking this differentiation to extremes that borders the absurdity.